"Until You Are Able": South Korean Multiculturalism and Hierarchy in My Little Hero. (26th March 2015) - Oh, David C.; Oh, Chuyun
Abstract: My Little Hero (2013) is the first popular Korean film to focus on an immigrant narrative that features a non-Korean or biracial Korean-White lead. In the story of a young Filipino-Korean boy's "Korean dream" to be accepted by his father/birth country and his reluctant and cynical teacher, the film reifies dominant Korean discourses of multiculturalism that are situated within local and global hierarchies. Locally, Korean multiculturalism looks down, requiring the non-White multiethnic other to integrate into dominant culture. Globally, it looks up to seek the paternal acceptance of the United States. In the film, multicultural discourses work to support the instrumental assimilation of the multiethnic other for the purposes of assimilating Korea within the ranks of "advanced" countries.